AN ANALYSIS OF THE SPEAKING FLUENCY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Zahra, Isnaini Az; Azhar, Fadly; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to analyze the speaking fluency levels of fourth-semester students in the English Language Education Study Program at FKIP Universitas Riau. Speaking fluency is essential for future English educators, as it reflects language proficiency and supports effective teaching processes. This research uses a descriptive quantitative method to assess fluency based on disfluency indicators, such as repetitions, pauses, fillers, and false starts. Data were collected through two-minute speech recordings of each participant, with a random sample of 27 students chosen from three classes. Spectral analysis using Audacity software identified and counted disfluencies, which were then statistically analyzed. Results show that most students achieved fluency at level 3, with high rates of pauses and fillers. Disfluency factors include limited vocabulary, speaking anxiety, and lack of English practice. Recommendations for enhancing fluency include gradually increasing task difficulty, providing more practice time, and offering in-depth learning materials. The study suggests that the program pay special attention to developing teaching materials and methods to support students’ fluency improvement.Keywords: Speaking fluency, disfluency, students, English language learning